2022
DOI: 10.1371/journal.ppat.1010736
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 is part of a galectin 8 dependent membrane damage recognition complex and drives autophagy upon Adenovirus endosomal escape

Abstract: Intracellular pathogens cause membrane distortion and damage as they enter host cells. Cells perceive these membrane alterations as danger signals and respond by activating autophagy. This response has primarily been studied during bacterial invasion, and only rarely in viral infections. Here, we investigate the cellular response to membrane damage during adenoviral entry. Adenoviruses and their vector derivatives, that are an important vaccine platform against SARS-CoV-2, enter the host cell by endocytosis fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Adenovirus enters cells through endocytosis and damages lysosomes by releasing its protease, enabling access to the cytosol for replication(A. Barlan et al, 2011; Greber et al, 1996; Pied et al, 2022; Wiethoff et al, 2015). We employed the wildtype human adenovirus species C2 (HAdV-C2 WT ) and its protease-deficient mutant TS1 (HAdV-C2 TS1 ), the latter lacking the ability to damage lysosomes(Gallardo et al, 2021; Greber et al, 1996; Martinez et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Adenovirus enters cells through endocytosis and damages lysosomes by releasing its protease, enabling access to the cytosol for replication(A. Barlan et al, 2011; Greber et al, 1996; Pied et al, 2022; Wiethoff et al, 2015). We employed the wildtype human adenovirus species C2 (HAdV-C2 WT ) and its protease-deficient mutant TS1 (HAdV-C2 TS1 ), the latter lacking the ability to damage lysosomes(Gallardo et al, 2021; Greber et al, 1996; Martinez et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…TBK1 is well characterized for phosphorylating multiple physiologically important substrates related to innate immunity and organelle quality control (Fitzgerald et al, 2003; Harding et al, 2021; Moore and Holzbaur, 2016; Pied et al, 2022; Weidberg and Elazar, 2011). However, two unbiased phospho-proteomics studies identified Rab7 as a major target for TBK1 (Heo et al, 2018; Ritter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cells must also monitor and manage lysosome integrity to ensure that lysosomes remain intact and lysosomal enzymes do not leak into the cytoplasm (Bohannon and Hanson, 2020; Yang and Tan, 2023). When lysosomes suffer severe damage that cannot be repaired, TANK-binding kinase 1 (TBK1) helps cells to clear severely damaged lysosomes via the process known as lysophagy where the damaged lysosomes are engulfed by autophagosomes and then delivered to intact lysosomes for degradation (Eapen et al, 2021; Hung et al, 2013; Maejima et al, 2013; Pied et al, 2022; Vargas et al, 2023). TBK1 also plays important roles in the autophagic clearance of damaged mitochondria and in signaling related to innate immunity (Fitzgerald et al, 2003; Harding et al, 2021; Heo et al, 2018; Moore and Holzbaur, 2016; Pomerantz and Baltimore, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This orchestrated response not only aids in combating viral infections but also assumes a central role in the broader antiviral defense mechanism of the host organism. Furthermore, TBK1’s influence extends beyond the realm of immune responses, encompassing essential cellular processes such as autophagy and mitochondrial quality control ( Pied et al, 2022 ). Its association with autophagy underscores its role in the degradation and recycling of impaired cellular constituents, thereby contributing to cellular homeostasis and survival ( Xiao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%